Case report: Directional infusion of peripheral blood stem cells into the necrotic zone in femoral heads through the medial circumflex femoral artery: A tracing study - Mao, Qiang; Shao, Weijie; Lv, Shuaijie; Tong, Peijian; He, Bangjian (Frontiers in Medicine, 2022)
Objective: This study aimed to explore whether peripheral blood stem cells (PBSCs) infused through the medial circumflex femoral artery to treat osteonecrosis of the femoral head (ONFH) could migrate into the necrotic area of femoral head. Methods: We collected PBSCs from a patient who had bilateral ONFH by apheresis technique using COBE spectra apheresis system (COBE BCT Inc, Lakewood, CO, USA) after subcutaneous injections of granulocyte-colony stimulating factor (G-CSF) at a dosage of 10 μg/kg for 4 days to mobilize PBSCs. After that, 100 MBq 2-[18F]-fluoro-2-deoxy-D-glucose (18F-FDG) was used to label PBSCs. 18F-FDG labeled PBSCs were infused into the left femoral head via the medial circumflex femoral artery to treat ONFH. Then the patient was underwent three-dimensional positron emission tomography (3D-PET) examination 60 minutes after cell infusion to monitor the biological distribution of 18F-FDG-labeled PBSCs, and to observe whether the transplanted PBSCs could migrate into the necrotic area of femoral head. Results: The total number of monouclear cells in the peripheral blood stem cell suspension was 1.95×108 which contained 2.20×106 CD34+ cells. The activity of 18F-FDG in the labeled cells was 1.8Bq/103 monouclear cells. 3D-PET imaging showed that 18F-FDG radioactivity was detected in the necrotic area of femoral head, acetabulum and femoral bone marrow cavity after transplantation of 18F-FDG-labeled PBSCs via the medial circumflex femoral artery. It is worth noting that although PBSCs labeled with 18F-FDG were widely distributed around the hip,such as femoral bone marrow cavity, femoral head and acetabulum, PBSCs were generally located in the necrotic area of femoral head. Conclusions: PBSCs could enter into the femoral head and migrate into the necrotic field of femoral head participating in the repair of osteonecrosis after infusion through the medial circumflex femoral artery.